Idham Chalid di Nahdlatul Ulama - Hidayatullah, Nur (Idrak: Journal of Islamic Education, 2018)
Nahdlatul Ulama is an Islamic organization in Indonesia, which until now exist in themiddle of the community, and has branches in several countries. NU interest manypeople because of its universal fikrah; founded by Hadratus Sheikh KH. Hasyim Asy’arisince before the independence of the Republic of Indonesia, 1926.Its existence until now of course after going through colorful political system at thattime, beginning from the physical revolution, the old order (orde lama), the new order(orde baru), up to the present democratic era. NU was led by Chairman of the NU, one ofthe chairmen is KH. Dr. Idham who contribute many things and successful lead within aperiod of 28 years (1956-1984) at times critical, such as receiving a guided democracy,Nasakom and periods of 1959 decree.There are many progress and struggles of Idham Chalid toward NU, both in the field ofeducation, economic, political, social and religious; NU gait also in the state and nation,as well as his contribution to the international world. Idham’s role as a leader of Islamicorganizations and also as a statesman who concurrently various legislative and executivepositions, from the old order to new order, giving a conclusion that religion and stateshould be hand in hand and mutually reinforcing.